Analisis Kepuasan Masyarakat Terhadap Pelayanan Publik Berdasarkan Indeks Kepuasan Masyarakat Pada Dinas Pendidikan Dan Kebudayaan Kabupaten Hulu Sungai Utara - Husaini, M. (STIA Bina Banua Banjarmasin, 2025)
The aim of this research is to find out how good the services provided by the North Hulu Sungai Regency Education andCCulture Office are based on the Community Satisfaction Index.This study employs a qualitative approach to explore phenomena in depth. This descriptive research was conducted in May 2024 and used CommunityCSatisfaction Index analysis. Non-probability sampling with an accidental type was used, and data collection was carried out through observation, documentation and questionnaires. The results of the research show that the services of the North Hulu SungaiCRegency Education and Culture Service have a Community Satisfaction Index (IKM) of 79.46 and public serviceCperformance is in the good service quality category.